Education on Work Discipline and Economic Ethics from the Perspective of Islamic Economics at PT Naura Sukses Abadi, Pasar Kemis District, Tangerang Regency - Resta Janiati Mega Utami; Muflih Adi Laksono (International Research and Development for Human Beings (IRDH), 2025)
This research and community activity was carried out through a seminar at PT Naura Sukses Abadi, Pasar Kemis District, Tangerang Regency, with the aim of providing an understanding of the importance of work discipline and economic ethics from the perspective of Islamic economics. Work discipline is understood as a form of obedience to rules, time, and responsibility, while Islamic economic ethics emphasizes the values of justice, trustworthiness, and efficiency in line with Islamic principles. The implementation method was conducted through an interactive seminar approach involving company employees with discussions, case studies, and reflections on work experiences. The results of the activity showed an increase in employees' awareness of the importance of discipline and Islamic work ethics as a foundation for enhancing productivity and the company’s integrity. This activity is expected to strengthen the Islamic work culture within PT Naura Sukses Abadi and serve as a model for the application of Islamic economic values in the industrial world.